Podróż na Syberię w świetle wspomnień Floriana Bohdanowicza - Wiech, Stanisław (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2018)
Florian Bohdanowicz is a translator of Georg Kennan’s book “Siberia”, which has been banned many times in Russia. He was sentenced for five years of exile to Siberia in 1879 for belonging to revolutionary organizations by the Military Court in Kiev. His journey through Siberia to the destination, that is, the gold mine on the river Kara, lasted nearly eight months. The journey, which he traveled successively: by rail (summer), steamboat (autumn), on foot and kibitki (in winter), in an extremely interesting way, he described in little-known memories. According to Bogdanowicz’s memoirs, the hardest parts of the prisoners’ journey to Siberia were the steamer cruise and their stay in prisons (in Kiev, Mcensk, Tyumen, Krasnoyarsk and Irkutsk).